1272 Effects of metal-rich particulate matter exposure on epstein-barr virus and human endogenous retrovirus w (herv-w) methylation healthy steel-workers. (24th April 2018) - Bollati, V; Bonzini, M; Mercorio, R; Angelici, L; Mariani, J; Delbue, S; Apostoli, P; Pesatori, AC
Abstract : Introduction: Inhaled particulate pollutants have been shown to produce systemic changes in DNA methylation. Global hypomethylation has been associated to viral sequence reactivation, possibly linked to the activation of pro-inflammatory pathways occurring after exposure. We aimed at evaluating the effects of PM exposure on DNA methylation of the Wp promoter of the Epstein-Barr Virus (EBV-Wp) and the promoter of the human-endogenous-retrovirus w (HERV-w), chosen as a paradigm of an exogenous virus and an endogenous retroviral sequence, in workers in an electric furnace steel plant with well-characterised exposure to metal-rich particulate matter. Methods: We measured EBV-Wp and HERV-w DNA methylation through bisulfite PCR Pyrosequencing on peripheral blood leukocytes DNA obtained from 63 male healthy workers, on the first day of a work week (baseline, after 2 days off work) and after 3 days of work (post-exposure). We determined individual exposure to inhalable particles and metals for all subjects. Paired t-test was used to compare baseline and post-exposure samples. Linear mixed models were fitted to evaluate the association between metal-rich particle exposure and DNA methylation. Results: Comparing samples obtained at baseline and after 3 days of work, the mean methylation of EBV-Wp was significantly higher at baseline compared to post-exposure (baseline=56.7; postexposure=47.9; p-value=0.009), whereas the mean methylation of HERV-w did not significantly differ. In a regression model adjusted for age, body mass index and smoking, nickel, arsenic and lead had a positive association with EBV-Wp methylation (nickel: β=16.16, p-value<0.001; arsenic: β=13.0, p-value=0.02; lead: β=16.53, p-value<0.001). Conclusions: The difference observed comparing baseline and postexposure samples may be suggestive of a rapid change in EBV methylation induced by air particles, while correlation between EBV methylation and metal exposure may represent an adaptive mechanism that should be further characterised in future investigations.